2021
DOI: 10.15326/jcopdf.2020.0170
|View full text |Cite
|
Sign up to set email alerts
|

Black Carbon Content in Airway Macrophages is Associated with Reduced CD80 Expression and Increased Exacerbations in Former Smokers With COPD

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…This study also identified a similar association with greater odds of a severe exacerbation. Furthermore, consistent with that prior study of former smokers with COPD [15] and a study by Kulkarni et al of children with asthma, [32] we identified an association with worse lung function. There is no established MCID for FEV 1 % predicted, however regulators have noted a change of 5-10% of change from baseline is considered to be clinically important [35].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study also identified a similar association with greater odds of a severe exacerbation. Furthermore, consistent with that prior study of former smokers with COPD [15] and a study by Kulkarni et al of children with asthma, [32] we identified an association with worse lung function. There is no established MCID for FEV 1 % predicted, however regulators have noted a change of 5-10% of change from baseline is considered to be clinically important [35].…”
Section: Discussionsupporting
confidence: 92%
“…Compared to other studies of AM BC obtained via induced sputum, [14,15,32] participants from this study had a higher observed BC deposition. This may be because those studies were of children or former smokers with COPD.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations